2022
DOI: 10.1177/15593258211068998
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Antibacterial Efficacy of Gallium Nanoparticles Coated by Ellagic Acid

Abstract: Cancer is a mortality contributor worldwide, and breast cancer is the most common among women. Despite the numerous breast cancer therapeutic strategies, they either have limitations or sometimes are resisted by cancer, so new approaches are needed to tackle those restrictions. Nanotechnology offers exciting leaps in the diagnosis and treatment of cancer, especially breast cancer. The main objective of this study was to investigate the effect of the newly synthesized gallium nanoparticles coated by Ellagic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…El-Sonbaty investigated the use of gallium nanoparticles coated in ellagic acid against the Gram-positive pathogens S. aureus , B. subtilis , and Bacillus cereus in a disc diffusion assay. They observed modest levels of inhibition with zones of inhibition ranging from 10 to 14 mm, all of which were smaller than their reference drugs …”
Section: Gallium Pharmacokinetics and Formulationsmentioning
confidence: 87%
See 1 more Smart Citation
“…El-Sonbaty investigated the use of gallium nanoparticles coated in ellagic acid against the Gram-positive pathogens S. aureus , B. subtilis , and Bacillus cereus in a disc diffusion assay. They observed modest levels of inhibition with zones of inhibition ranging from 10 to 14 mm, all of which were smaller than their reference drugs …”
Section: Gallium Pharmacokinetics and Formulationsmentioning
confidence: 87%
“…They observed modest levels of inhibition with zones of inhibition ranging from 10 to 14 mm, all of which were smaller than their reference drugs. 174 Best et al used three different polysaccharides, carboxymethyl cellulose (CMC), alginate, and pectin, as delivery vehicles for gallium. They were then tested against P. aeruginosa, E. coli, and S. aureus by finding their MICs, and minimum bactericidal concentrations (MBCs).…”
Section: Gallium Pharmacokinetics and Formulationsmentioning
confidence: 99%
“…It was also confirmed as hepatoprotective and renoprotective in the course of in vivo testing against 7, 12 dimethylbenz[a] anthracene (DMBA)-induced mammary gland carcinogenesis in rats. Yet again, the authors did not specifically investigate the possible ferroptotic character of the reported cellular response, focusing on how efficient the antitumor activity was, but a few relevant observations can be made [ 75 ]. The nanoparticles decreased the level of alanine transaminase and aspartate aminotransferase.…”
Section: Gallium Salts Complexes and Nanoparticlesmentioning
confidence: 99%
“…Less malondialdehyde, on the other hand, was indicative of an inhibited lipid peroxidation process in cancer cells [ 78 ]. The gallium atoms likely contributed to normalizing the serum level of iron, as reflected by lower total iron-binding capacity (TIBC) relative to the DMBA iron-deficient group, where much of iron supply was consumed by malignant cells [ 75 ]. How much of the reported antitumor effect was related to the ferroptosis-inducing properties of the gallium-based agent remains up for debate.…”
Section: Gallium Salts Complexes and Nanoparticlesmentioning
confidence: 99%
“…Pomegranate fruit extract (PFE) shows antioxidative activity caused by the action of EA . Research findings show that EA is a potential biomolecule with remarkable biological features, such as UV shielding and anticancer functionalities. It is also a potent antioxidant and antibacterial agent. , EA is made up of four hydroxyl groups and several lactone rings, which are hydrophilic . However, its low bioavailability limits its therapeutic effect .…”
Section: Introductionmentioning
confidence: 99%